Improvement of the catalytic activity and thermostability of a hyperthermostable endoglucanase by optimizing N-glycosylation sites - Han, Chao (Biotechnol Biofuels, 2020)
BACKGROUND: Endoglucanase has been extensively employed in industrial processes as a key biocatalyst for lignocellulosic biomass degradation. Thermostable endoglucanases with high catalytic activity at elevated temperatures are preferred in industrial use. To improve the activity and thermostability, site-directed mutagenesis was conducted to modify the N-glycosylation sites of the thermostable β-1,4-endoglucanase CTendo45 from Chaetomium thermophilum. RESULTS: In this study, structure-based rational design was performed based on the modification of N-glycosylation sites in CTendo45. Eight single mutants and one double mutant were constructed and successfully expressed in Pichia pastoris. When the unique N-glycosylation site of N88 was eliminated, a T90A variant was active, and its specific activity towards CMC-Na and β-d-glucan was increased 1.85- and 1.64-fold, respectively. The mutant R67S with an additional N-glycosylation site of N65 showed a distinct enhancement in catalytic efficiency. Moreover, T90A and R67S were endowed with extraordinary heat endurance after 200 min of incubation at different temperatures ranging from 30 to 90 °C. Likewise, the half-lives (t(1/2)) indicated that T90A and R67S exhibited improved enzyme thermostability at 80 °C and 90 °C. Notably, the double-mutant T90A/R67S possessed better hydrolysis activity and thermal stability than its single-mutant counterparts and the wild type. CONCLUSIONS: This study provides initial insight into the biochemical function of N-glycosylation in thermostable endoglucanases. Moreover, the design approach to the optimization of N-glycosylation sites presents an effective and feasible strategy to improve enzymatic activity and thermostability.